The Limits of Philology: Aulus Gellius, NA 2.9 - Alberto J. Quiroga Puertas (Ágora, 2013)
This paper aims to study the use of the Greek verb λεξιθηρέω in Aulus Gelliusʹ Noctes Atticae. Its coinage in the work of the Roman author is indicative of a cultural programme, and reflects contemporary concerns on the appropriate use of language.